(untitled) (Communications in Computational Physics, 2020)
Wing planform is one of important factors for lift and thrust generation and enhancement in flapping flight. In this study, we numerically investigate the effect of wing planform on aerodynamic performance of a butterfly-like flapping wing-body model by using the immersed boundary-lattice Boltzmann method. The model flaps downward for generating the lift force and backward for generating the thrust force like an actual butterfly. We calculate the aerodynamic performance such as the lift force, the thrust force, the power expenditure, and the power loading for (i) trapezoidal wing planforms with various taper ratios (ratio of the wing-tip length to the wing-root length), (ii) rectangular wing planforms with various aspect ratios (ratio of the square of the wing length to the wing area), and (iii) an actual butterfly's wing planform at the Reynolds number of 500. As a result for the trapezoidal and rectangular wing planforms, we find that the lift and thrust forces increase at the cost of the power expenditure as the taper ratio increases and as the aspect ratio increases. In addition, it is found that the actual butterfly's wing planform is more efficient than any of the trapezoidal and rectangular wing planforms.